Colonialism and Image in the Archaeological Expeditions in French Africa (1922-1925) - García Sánchez, Jorge (Hispania Nova, 2023)
This article delves into the photographic and cinematographic production resulting from the excavations and explorations of the dilettante archaeologist Byron Khun de Prorok in Tunisia and the Algerian desert. Interested in seducing the public with his quests, Prorok was gradually lowering the standards of veracity in his writings and the images that illustrated them. These, as well as the scenes of his films, also responded to conventionalisms and prejudices typical of colonial archaeology, which are aligned with the orientalism prevailing at the time. They also show how the dissemination of archaeological science acted as a vehicle for spreading French colonial action in North Africa.
Keywords: Carthage; orientalism; tophet; press; photographie